Evaluación de la implementación de los patrones no convencionales para la inyección continua de vapor en el área X con simulación dinámica en CMG (2021)
The main objective of the following project is to evaluate the effectiveness of the application of unconventional standards for the application of continuous steam injection, being used as an improved recovery technique for the area under study, which consists of the principle of decreasing viscosity from of the heat transfer between the injected steam and the fluid in the reservoir, the area had been operating through an alternate injection of steam, having condensation problems of the injected steam, thus generating problems due to the capillary pressure and consequently for the displacement of the reservoir fluids, to solve this it is proposed that through a continuous injection the change in viscosity is generated and the fluid displacement is improved.